EFFECTS OF ECONOMIC STRESS ON MARITAL QUALITY AND STABILITY - Šakotić-Kurbalija, Jelena; Trifunović, Biljana; Kurbalija, Dragan (Primenjena psihologija, 2017)
The main aim of this study was to examine the contribution of economic stress to perception of the marital quality and stability. Study was conducted on a sample of 2049 Serbian women, including married and women in cohabiting relationships, aged 19 to 75 years, with different socioeconomic status. The quality of the marital relations was measured by the Dyadic Adjustment Scale (DAS: Spanier, 1976), and marital instability was estimated by the Marital Instability Index (Booth, Johnson, & Edwards, 1983). In adition to existence of economic hardship (e.g., the ratio of monthly income and spending, financial burden, etc.), we also measured women's subjective level of stress. Contribution of economic stress to (in)stability and perception of the marital quality has been tested by multiple regression analysis. Both models have proved to be statistically significant, with 4% of the explained variance of marital instability, and 8% of the explained variance of marital quality. Significant, but small contributions to the explanation of marital instability generated two independent variables - ratio of monthly income and spending and the existence of debt, while significant predictors of marital quality were: ratio of monthly income and spending, monthly income, long-term loans, changes related to the men's job, and the existence of debt. The results obtained in this study are similar to the findings of previous studies conducted in countries in transition and suggest that economic difficulties have a negative effect on marital processes.